Economics of Veterinary Services Delivery among Commercial Poultry Farmers in a Market-Driven Economy: Evidence from Delta State, Nigeria - Achoja, F.O.; Ike, P.C.; Akporhuarcho, P.O. (International Journal of Poultry Science, 2010)
The economics of veterinary services delivery among commercial poultry farmers was investigated using primary data collected from 60 respondents (50 commercial poultry farmers and 10 veterinary officers) with the aid of structured questionnaire. Data collected were analyzed using a combination of descriptive statistics (i.e. mean, percentage, standard deviation, table) and inferential statistics (i.e. multiple regression model). The results of the study showed that though the veterinary services delivery was structured into public and private sectors majority (60.9%) of the commercial poultry farmers demanded and obtained veterinary services from the public sector. The estimated cost function of commercial poultry farm in the study area revealed that the cost of veterinary services significantly affected the total cost of poultry output (p = 0.01). The estimated demand function for veterinary services indicated that the scale of production and distance to the nearest veterinary office were the significant determinants of the demand for veterinary services in the study area. The finding of the study further revealed that the propensity to supply veterinary services was mainly influenced by demand of poultry farmers (0.8) and effective price that they are willing to pay (0.8). It was recommended among others that private individuals should be encouraged by policy to participate in veterinary services delivery. The issue of veterinary services should be considered important in any development programme in the poultry industry in Delta State, Nigeria.